Determinants of viewers' choice on private news channels - Himali, L.P.; Kuruwitage, R. (university of Jaffna, 2014)
Viewers' choice for the news channels is a physiological phenomenon, varies for each viewer. The future of any economic entity is determined by the customers' choice. Private news channels use various strategies to attract viewers to face the high competition of the news channels industry in Sri Lanka. The main objective of the study is to identify viewer characteristics and factors affected to the viewers' choice on private news channels. Primary data was mainly used by the study through a questionnaire. 25 academic staff members and 25 nonacademic staff members, 25 students in Sabaragamuwa University of Sri Lanka and 25 villages in Pabahinna Grama Niladhari division were selected by the study by using a convenience sampling method. Chi square test statistic was used to identify the determinants. Study found that viewers' political party, residential sector, age of the viewer, choice of family members, time that the news telecasted, coverage and reliability of the broadcasted news are the very important factors that the viewers' consider before choosing a news channel. The most significant fact revealed by the study is that gender, level of education and working status of the person are not the basic reasons for selection of a news channel. Most of viewers are rural resident and 100% of urban resident watching privet news channels. Females are watch news than males. Approximately more than 70% of the subjects watch Hiru TV news and therefore according to this study famous private news channel is Hiru TV.
Keywords: Determinants; News channel; Viewer choice